Zakaz reformationis in peius w dawnym i współczesnym procesie cywilnym - Smyk, Grzegorz (PRAWO i WIĘŹ, 2025)
The issue of the objective limits of adjudication and the ruling of the appellate court is closely related to the institution of the prohibition of reformationis in peius. This term is used to describe the prohibition of the appellate court to review the merits of the case to the detriment of the party who has appealed against the lower court's decision, if the opposing party has not appealed. In the historical development of the civil process, the institution of the prohibition of reformationis in peius developed differently in individual procedural systems. In the Roman trial of the pre-Justinian period, the prohibition of reformationis in peius was in effect due to the fact that the court was strictly bound by the boundaries and direction of the appeal, which it could not cross due to the principle of ultra petita non cognoscitur. This practice was changed in Justinian times when the Lex Amploirem allowed the court to rule regardless of the direction of the appeal. The Justinian regulation influenced the removal of the grounds for this prohibition in the German common civil trial, where, following the example of the Lex Ampliorem, the appellate court could adjudicate ex officio. However, in most European procedural systems, which adopted the native and fully complaints form of civil proceedings, the prohibition of reformationis in peius was a natural consequence of the dispositivity principle. The emergence of a new type of civil procedure at the turn of the 19th century, in which the prohibition of reformationis in peius was recognised as a principle of appeal, led to its definition and formulation in the form in which it functions to this day. It was at that time that the dogmatic grounds for binding the court with it were established, and then its functions and normative form.